Discrepancy between subjective and objective postoperative oral dysfunction assessment after oral cancer treatment: A single-center cross-sectional study. (June 2022) - Kato, Akira; Matsuda, Yuhei; Morioka, Reon; Okui, Tatsuo; Okuma, Satoe; Tatsumi, Hiroto; Kanno, Takahiro
Highlights: In case of postoperative oral dysfunction type III (occlusal type), the subjective and objective evaluations tended to be consistent. Postoperative oral dysfunction type I (transport type) and II (oral hygiene type) may be prone to overestimation or underestimation by either the subjective or objective evaluations. Medical professionals should pay attention to patient complaints following oral cancer treatment. Abstract: Objectives: It has been reported that in many cancer types, the evaluation of complications and side effects of treatment differs between subjective and objective evaluations. The purpose of this study is to verify whether the evaluation of postoperative oral dysfunction following oral cancer treatment was consistent subjective and objective evaluations. Materials and Methods: This cross-sectional study collected background data and evaluated the oral function (microorganisms, oral dryness, occlusal force, tongue pressure, masticatory function and eating assessment tool [EAT-10]) of 75 patients from September 2019 to December 2021. The postoperative oral dysfunction-10 (POD-10) was used for the subjective assessment of dysfunction in oral cancer patients. Also, Matsuda-Kanno classification was used for the objective assessment. The kappa coefficient between POD-10 and oral dysfunction was calculated for the degree of agreement. The relationship between oral function measurements and POD-10 was examined by multiple regression analysis. Results: The patients' median age was 72.0 (25–75 percentile: 64.0–78.0) and 69.3% were male. The kappa coefficients indicating the degree of agreement with POD-10 were 0.41 (P < 0.01) for occlusal force, 0.27 (P = 0.01) for masticatory function, and 0.59 (P < 0.01) for EAT-10. Multiple regression analysis showed a significant association of occlusal force (β = −0.33, P = 0.03) and EAT-10 (β = 0.80, P < 0.01) with POD-10. Conclusions: For postoperative oral dysfunction type III (occlusal type), the evaluations of subjective and objective evaluations tended to be consistent. However, for type I (transport type) and II (oral hygiene type), these evaluations may be prone to overestimation or underestimation by either the medical professional or the patient.